2014
DOI: 10.1159/000365150
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analyses of Cognitive-Behavioural Therapy of Depression: A Systematic Review

Abstract: Background: Major depressive disorder (MDD) causes a massive disease burden worldwide. Cognitive behavioural therapy (CBT) is an important treatment approach for depression. Cost-utility analysis (CUA) is a method to support decisions on efficient allocation of resources in health policy. The objective of our study was to systematically review CUA of CBT in the treatment of patients suffering from MDD. Methods: We conducted a systematic literature search in Medline, Embase, PsycINFO and National Health Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…They, too, found IPT to have favorable cost-effectiveness results. Our findings also add to the larger literature demonstrating the cost-effectiveness of CBT to adult depression in general (Barret et al, 2005; Brettschneider et al, 2014; Wiles et al, 2016). For example, in a systematic review of 22 studies of CBT in varied formats with different populations, Brettschnieder et al concluded that most studies demonstrated acceptable incremental cost-utility ratios of <$50,000.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…They, too, found IPT to have favorable cost-effectiveness results. Our findings also add to the larger literature demonstrating the cost-effectiveness of CBT to adult depression in general (Barret et al, 2005; Brettschneider et al, 2014; Wiles et al, 2016). For example, in a systematic review of 22 studies of CBT in varied formats with different populations, Brettschnieder et al concluded that most studies demonstrated acceptable incremental cost-utility ratios of <$50,000.…”
Section: Discussionsupporting
confidence: 74%
“…Cost-effectiveness analyses guide decision makers in selecting and paying for certain treatments over others given limited resources. Despite a broad consensus that such studies are important to clinical decision-making (Hill, 2012), relatively few such analyses have been undertaken in the treatment of depression generally (Barrett et al, 2005; Brettschneider et al, 2014) or for maternal depression in particular (Dennis, 2005). For cognitive behavioral therapy (CBT) as a treatment of depression in adults, findings have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Economic evidence is available for depression treatment in adolescents, although it remains inconclusive whether selective serotonin reuptake inhibitors (SSRIs) alone or SSRI plus cognitive behavioural therapy (CBT) is more cost‐effective, with two earlier randomized controlled trials (RCTs) providing conflicting evidence. In another review, the authors noted that, in children and adolescents, CBT is unlikely to be cost‐effective compared with medication. When CBT is used as second‐line intervention for depressed young people declining antidepressants, a recent RCT has suggested dominance of CBT over treatment as usual by the end of 24 months, but not 12 months.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…As one of the most well‐studied interventions for depression and anxiety, CBT has been frequently evaluated in economic analyses. In a systematic review of CUA from 22 studies published between 2004 and 2012 on CBT for major depressive disorder, the authors concluded that most studies showed “acceptable incremental cost‐utility ratios”.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…In contrast, a more recent systematic review, investigating the costutility of CBT for depression, found evidence that individualized CBT for adults as stand-alone treatment or in combination with antidepressants is cost-effective in comparison to usual care and that it is not inferior to medication (Brettschneider et al, 2015).…”
Section: Societal Costsmentioning
confidence: 93%